AC corrosion analysis of the buffer layer in HV corrugated-aluminum sheathed power cables. (September 2022) - Kong, Jiamin; Zhou, Kai; Meng, Pengfei; Zhao, Qi; Wu, Yaping; Ren, Xianchen; Chen, Yidong
Highlights: Differences in compositions of the white powder at different place in a cable. Generation mechanism and property of white powder on buffer layer. Quantitative characterization of the corrosion by AC current density spectroscopy. Factors on electrochemical corrosion of buffer layer in cable. Relationship between electrochemical corrosion of buffer layer and final failure. Abstract: Here we examine the AC corrosion characteristics of the buffer layer in high voltage corrugated-aluminum sheathed power cables, and analyze the relationship between corrosion and cable failure. Penetration of moisture into the buffer layer, including dampness introduced during manufacture and direct water entry through mechanical damage to the cable sheath, results in AC corrosion and formation of hydrogen and Al(OH)3 . On the basis of AC current density spectroscopy, the influences of voltage, moisture content, and pressure on the threshold current density are investigated. The cable structure is considered, and a relationship between the AC corrosion and cable failure is determined. A large ripple depth of the corrugated aluminum promotes a non-uniform circular current distribution. The combination of high moisture content and non-uniform current density results in local high temperatures in the buffer layer that ultimately cause the failure of the power cables.